Adaptively Targeted Models of Economic Forecast-ing by Supply Chain Management - Viktoriya I. Tinyakova; Valeriy V. Davnis; Manya A. Ziroyan; Sun Xingyuan (International Journal of Supply Chain Management, 2020)
Abstract- Forecasting is an under estimated field of research in supply chain management. Uncertainties inherent in customer demands make it difficult for supply chains to achieve just-in-time inventory replenishment, resulting in loosing sales opportunities or keeping excessive chain-wide inventories. In this paper, we propose two adaptive inventory-control models for a supply chain consisting of one supplier and multiple retailers. Development of an approach that provides the opportunity to construct models for the formation of multidimensional options that describe the forecast image of regions and municipalities. Agreeing with the thesis